The Impact of Antidiabetic Therapies on Diastolic Dysfunction and Diabetic Cardiomyopathy - Gopal, Keshav; Chahade, Jadin J.; Kim, Ryekjang; Ussher, John R. (Frontiers in Physiology, 2020)
Diabetic cardiomyopathy is more prevalent in people with type 2 diabetes mellitus (T2DM) than previously recognized, while often being characterized by diastolic dysfunction in the absence of systolic dysfunction. This likely contributes to why heart failure with preserved ejection fraction is enriched in people with T2DM versus heart failure with reduced ejection fraction. Due to revised mandates from major health regulatory agencies, all therapies being developed for the treatment of T2DM must now undergo rigorous assessment of their cardiovascular risk profiles prior to approval. As such, we now have data from tens of thousands of subjects with T2DM demonstrating the impact of major therapies including the sodium-glucose co-transporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 receptor (GLP-1R) agonists, and dipeptidyl peptidase 4 (DPP4) inhibitors on cardiovascular outcomes. Evidence to date suggests that both SGLT2 inhibitors and GLP-1R agonists improve cardiovascular outcomes, whereas DPP4 inhibitors appear to be cardiovascular neutral, though evidence is lacking to determine the overall utility of these therapies on diastolic dysfunction or diabetic cardiomyopathy in subjects with T2DM. We herein will review the overall impact SLGT2 inhibitors, GLP-1R agonists, and DPP4 inhibitors have on major parameters of diastolic function, while also highlighting the potential mechanisms of action responsible. A more complete understanding of how these therapies influence diastolic dysfunction will undoubtedly play a major role in how we manage cardiovascular disease in subjects with T2DM.